Improved Survival Among Hospitalized Patients With Coronavirus Disease 2019 (COVID-19) Treated With Remdesivir and Dexamethasone. A Nationwide Population-Based Cohort Study. (10th June 2021) - Benfield, Thomas; Bodilsen, Jacob; Brieghel, Christian; Harboe, Zitta Barrella; Helleberg, Marie; Holm, Claire; Israelsen, Simone Bastrup; Jensen, Janne; Jensen, Tomas Østergaard; Johansen, Isik Somuncu; Johnsen, Stine; Lindegaard, Birgitte; et al.
Abstract: Background: There are limited data on outcomes of moderate to severe coronavirus disease 2019 (COVID-19) among patients treated with remdesivir and dexamethasone in a real-world setting. We sought to compare the effectiveness of standard of care (SOC) alone versus SOC plus remdesivir and dexamethasone. Methods: Two population-based nationwide cohorts of individuals hospitalized with COVID-19 during February through December 2020 were studied. Death within 30 days and need of mechanical ventilation (MV) were compared by inverse probability of treatment weighted (ITPW) logistic regression analysis and shown as odds ratio (OR) with 95% confidence interval (CI). Results: The 30-days mortality rate of 1694 individuals treated with remdesivir and dexamethasone in addition to SOC was 12.6% compared to 19.7% for 1053 individuals receiving SOC alone. This corresponded to a weighted OR of 30-day mortality of 0.47 (95% CI: .38–.57) for patients treated with remdesivir and dexamethasone compared to patients receiving SOC alone. Similarly, progression to MV was reduced (OR 0.36; 95% CI: .29–.46). Conclusions: Treatment of moderate to severe COVID-19 during June through December that included remdesivir and dexamethasone was associated with reduced 30-day mortality and need of MV compared to treatment in February through May. Abstract : Treatment of moderate to severe coronavirus disease 2019 (COVID-19) with remdesivir and dexamethasone was associated with a lower risk of mechanical ventilation and a significant better overall 30-day survival as compared to standard care alone.